Unicorn tears : why startups fail and how to avoid it - Pride, Jamie (John Wiley & Sons Australia, Ltd, 2018)
The real-world secrets to startup success Unicorn Tears is the smart entrepreneur's guide to startups. A full 92% of startups fail in the first three years-but failure is not inevitable. Most of these companies self-sabotage, unconsciously eliminating any chance at success before they even get started. It's not the economy, it's not politics, it's not external factors; failure comes from within. This book shows you how to be one of the unicorns-one of the 8% who make it. Be prepared to un-learn everything you thought you knew about startups, as author Jamie Pride busts the harmful myths that lead so many companies to failure. Drawing upon his history as a venture capitalist, he reveals what investors want to see and hear, and what final factor puts your venture firmly into the "yes" column. Pride understands what matters in startups, and what gets in the way; his Hollywood Method for start-up success gives you a proven formula based on the tried-and-true framework Hollywood uses to make movies that succeed around the globe. Case studies illustrate what success looks like on the ground, and brings a global perspective to successful entrepreneurship and the strategies that help your business grow.-Learn the truth behind the eight myths of startups -Adopt a proven formula for success based on Hollywood blockbusters -Craft a winning pitch to bring investors-and capital-over to your side -Gain real-world perspective on startups and future trends Everyone wants their business to succeed, but wanting means nothing without a solid plan and the means to implement it. Unicorn Tears helps you set yourself up for success, and gives you the tools to forge your path to the top